Intra-Arterial Chemotherapy as Primary Treatment for Advanced Unilateral Retinoblastoma in China - Liang, Tingyi; Zhang, Xin; Li, Jiakai; Hua, Xuming; Zhao, Peiquan; Ji, Xunda (Frontiers in Medicine, 2022)
Purpose: This study aimed to evaluate the efficacy and complications of intra-arterial chemotherapy (IAC) as a primary treatment for advanced unilateral retinoblastoma in Chinese patients. Methods: This study was a retrospective review of patients with advanced unilateral retinoblastoma treated with IAC as the primary treatment. The IAC procedures were performed using a balloon-assisted technique. The clinical status and treatment complications were recorded at each visit. Kaplan–Meier analysis was performed to estimate recurrence-free survival and ocular survival. Results: In total, 116 eyes of 116 patients with advanced unilateral retinoblastoma were enrolled, including 66 eyes (57%) in group D and 50 eyes (43%) in group E. All treated eyes received a mean of 3 cycles of IAC (range, 3–5), and 66% of the eyes were combined with local consolidation therapy. The median follow-up time was 39 months (range, 22–57 months). The 3-year recurrence-free survival and ocular survival rates were 68.8% (95% CI, 59.2%–76.6%) and 88.5% (95% CI, 80.9%–93.2%), respectively. Moreover, the 3-year ocular survival rate in group D was significantly higher than that in group E (96.9%, 76.3%; P < 0.01). The common ocular complication was vitreous hemorrhage (19.8%). No deaths or severe systemic complications occurred. Conclusion: Primary intra-arterial chemotherapy is effective for the treatment of advanced unilateral retinoblastoma, especially in group D, with acceptable toxicity.